Patient safety management activities partially mediate nursing competences and patient safety culture in Vietnam - Binh Ho Duy; Phuc Dang Thi Thanh; Nhi Vo Thi; Yen Ho Thi My; Nguyen Nguyen Binh Thao; Quyen Tran Thi Kim; Lan Duong Thi Ngoc (PLoS ONE, 2026)
Background Patient safety culture is a key determinant of healthcare quality, yet evidence remains limited on how nurses’ person-centered care competence and patient safety competence relate to patient safety culture through patient safety management activities, particularly in low- and middle-income settings. Objective To describe levels of person-centered care competence, patient safety competence, patient safety management activities, and patient safety culture among nurses in central Vietnam, and to examine their direct and indirect relationships using a mediation model. Methods A multicenter cross-sectional study was conducted among 1,036 nurses from five tertiary hospitals in central Vietnam (response rate 99.6%). Person-centered care competence was measured using P-CAT, patient safety competence using H-PEPSS, patient safety management activities using PSMA, and patient safety culture using HSOPSC. Descriptive statistics, Pearson correlations, and multivariable linear regression analyses were performed. Mediation effects were examined using bias-corrected bootstrapping with 5,000 resamples. Results Mean scores indicated moderate-to-high levels of person-centered care competence (3.77 ± 0.36), patient safety competence (4.23 ± 0.36), and patient safety management activities (4.44 ± 0.35), while patient safety culture was moderate (3.93 ± 0.35). All variables were positively correlated, with the strongest association observed between person-centered care competence and patient safety culture (r = 0.49, p < 0.001). In adjusted regression analyses, person-centered care competence and patient safety competence were independently associated with patient safety management activities (β = 0.149 and β = 0.274; both p < 0.001). Patient safety management activities were significantly associated with patient safety culture (β = 0.102, p < 0.001). Bootstrapped analyses showed significant partial mediation through patient safety management activities for both person-centered care competence (indirect β = 0.0265, 95% CI 0.0143–0.0404) and patient safety competence (indirect β = 0.0497, 95% CI 0.0304–0.0711), suggesting that frontline safety behaviors may represent a pathway linking competencies to patient safety culture. Conclusions Higher person-centered care competence and patient safety competence were associated with stronger patient safety culture, partly through increased engagement in patient safety management activities. These findings highlight the potential role of patient safety management activities as a mechanism linking competencies to patient safety culture. However, causal relationships cannot be inferred due to the cross-sectional design.